Hashimoto's encephalopathy in a patient with septal panniculitis: a case report - C. Cosso; M. Ghio; M. Cutolo (PAGEPress Publications, 2018)
Hashimoto's encephalopathy (HE) is an autoimmune form of encephalopathy, associated with autoimmune thyroiditis. Its prevalence is estimated to be 2:100,000. HE is characterized by behavioral changes, mental confusion, dysarthria, ataxia, psychosis, paranoia, convulsions, hallucinations, headache and hyperthermia. Elevated thyroid antibodies are necessary for diagnosis and the disease responds dramatically to glucocorticoid therapy. We describe a patient with HE and panniculitis, an association reported twice in the literature.